1992
DOI: 10.1111/j.1365-2869.1992.tb00049.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep studies for sleep‐related breathing disorders

Abstract: SUMMARY Our understanding of sleep-related breathing disorders is still in a period of rapid change. Considerable uncertainty exists in several major areas of patient assessment. Although early definitions of sleep apnoea enshrined the concept of rigid guidelines, such an approach is no longer helpful, and may constrain potential advances. The recognition of the basic pathophysiological events in obstructive sleep apnoea (OSA) has evolved from purely apnoeas, to include hypopnoeas, and now to increased upper a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 27 publications
(15 reference statements)
1
15
0
2
Order By: Relevance
“…This means that by subtracting the value of the deep sleep output from that of the wakefulness output all three outputs can be combined, without significunt loss of information, into the single trace shown in Compared to the hypnogram, therefore, the network's outputs provide a much more accurate assessment of both sleep fragmentation and quality of sleep. Such an assessment is crucial to the study of sleep-related breathing disorders, where rule-based sleep staging has been shown to be unsuitable (Stradling 1992). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This means that by subtracting the value of the deep sleep output from that of the wakefulness output all three outputs can be combined, without significunt loss of information, into the single trace shown in Compared to the hypnogram, therefore, the network's outputs provide a much more accurate assessment of both sleep fragmentation and quality of sleep. Such an assessment is crucial to the study of sleep-related breathing disorders, where rule-based sleep staging has been shown to be unsuitable (Stradling 1992). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Daytime sleepiness results from the many transient arousals that fragment sleep in OSAHS and that are believed to be a response to the increases in inspiratory effort being made in an attempt to maintain adequate ventilation through a narrowed or collapsed upper airway [3,4].A respiratory sleep study to investigate OSAHS should therefore include either a measure of ventilatory effort or upper airway narrowing, and a measure of arousals as a marker of the resulting sleep fragmentation [5]. Because OSAHS is a relatively common disorder affecting 1-5% of the adult male population [6], and the financial resources for healthcare are limited, such respiratory sleep studies should also be cost-effective and, preferably, domiciliary [7].…”
mentioning
confidence: 99%
“…A respiratory sleep study to investigate OSAHS should therefore include either a measure of ventilatory effort or upper airway narrowing, and a measure of arousals as a marker of the resulting sleep fragmentation [5]. Because OSAHS is a relatively common disorder affecting 1-5% of the adult male population [6], and the financial resources for healthcare are limited, such respiratory sleep studies should also be cost-effective and, preferably, domiciliary [7].…”
mentioning
confidence: 99%
“…
aaBreathing airflow is a physiological variable commonly monitored for assessing respiratory patterns and nocturnal events in studies aimed at diagnosing sleep disorders [1][2][3]. Given that in sleep studies the use of a pneumotachograph, which is the reference transducer for measuring flow, is rather cumbersome, airflow is routinely assessed by means of thermally sensitive devices such as thermistors and thermocouples.
…”
mentioning
confidence: 99%